Method for preparing carbon material from waste lithium ion battery positive electrode material and adsorbing hydrogen bromide

By combining the used lithium-ion battery positive electrode material with biomass and reed waste to prepare carbon materials, the problems of low hydrogen bromide gas treatment efficiency and difficulty in recycling and utilization of lithium-ion batteries are solved, and efficient adsorption and green and environmentally friendly utilization of resources are achieved.

CN119175077APending Publication Date: 2024-12-24LANGFANG NORMAL UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411319110.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently treat hydrogen bromide gas, resulting in environmental pollution and waste of resources, and the recycling and green utilization of lithium-ion batteries has problems of high cost and low efficiency.

Method used

By combining the used lithium-ion battery positive electrode material with biomass and reed waste, carbon materials are prepared and used for the adsorption of hydrogen bromide under mild conditions, the efficient adsorption of carbon materials is achieved.

Benefits of technology

It realizes efficient adsorption of hydrogen bromide, solves the problems of resource waste and environmental pollution, has the advantages of green and environmental protection, simple operation and low cost, and promotes the resource utilization of lithium-ion battery positive electrode materials and biomass waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of industrial waste treatment, and relates to a method for preparing a carbon material by using a waste lithium ion battery positive electrode material and adsorbing hydrogen bromide, which comprises the following steps: mixing a eutectic solvent and a lithium ion battery positive electrode material in a mass ratio of (45-55): 1 at 110-130 DEG C for 23-25 hours, and centrifuging to obtain a leaching solution; uniformly mixing biomass and the leachate according to a mass ratio of 1: 1-1: 4, and calcining at 400-600 DEG C for 1.5-3 hours to obtain a carbon material; the carbon material is used for adsorbing hydrogen bromide gas or hydrogen chloride gas, the adsorption temperature is 25-60 DEG C, and the adsorption time is 24-72 hours. According to the method, hydrogen bromide gas is adsorbed by utilizing the prepared carbon material under mild conditions, so that the problems of resource waste and environmental pollution can be solved, and the method has important application value in resource utilization of lithium ion battery positive electrode material lixivium and reed and straw wastes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of industrial waste treatment, relates to the green resource application of waste lithium ion battery positive electrode materials, and specifically relates to a method for preparing carbon materials using waste lithium ion battery positive electrode materials and using the carbon materials for adsorbing hydrogen bromide. Background Art

[0002] Hydrogen bromide is widely used in industry to manufacture bromine compounds, catalysts in organic synthesis, etc. High-purity hydrogen bromide is mainly used for etching of phosphorus-doped polysilicon, single crystal silicon or two-dimensional semiconductors. It is one of the core gases in advanced chip technology and is widely used in advanced process fields of memory chips, logic chips and power semiconductors. Hydrogen bromide is an irritating gas and is corrosive. Improper discharge or accidental leakage will cause serious pollution to the atmosphere, water bodies and soil, and pose potential risks to human health. At present, traditional methods for treating hydrogen bromide have problems such as high cost, low efficiency and complex operation. Therefore, it is of great significance to prepare a new adsorbent to achieve efficient adsorption of hydrogen bromide.

[0003] Lithium-ion batteries are widely used in mobile power devices and electric vehicles. As the production and sales of lithium batteries increase year by year, the amount of scrapped lithium-ion batteries also increases. A large number of scrapped lithium-ion batteries will bring serious environmental problems. The recycling and green utilization of lithium-ion batteries have become an important issue for the sustainable development of the battery industry. Reeds are the main plants in Baiyangdian. Due to the transformation of economic development, the utilization rate of reeds is getting lower and lower, so reeds have become one of the main solid wastes. As the main agricultural waste, the harmful gases and particulate matter after burning of straw will cause pollution and even cause fires. Due to the large amount of reed waste and straw waste and the low utilization rate, they are still among the ranks of solid wastes.

[0004] Based on this, the present invention proposes a method for synthesizing carbon materials using biomass and lithium-ion battery positive electrode material leachate as raw materials. The prepared carbon material is used to adsorb hydrogen bromide, realizing the environmental protection concept of "treating waste with waste", and has high social value. Summary of the invention

[0005] The purpose of the present invention is to solve the above-mentioned problems existing in the prior art. A method for preparing a carbon material using the positive electrode material of waste lithium-ion batteries and using the carbon material for adsorbing hydrogen bromide is proposed. The method makes green resource utilization of lithium-ion batteries in the retired period, and can make full use of reed waste and straw waste, and has the advantages of low cost and low energy consumption.

[0006] The technical solution of the present invention is:

[0007] A method for preparing a carbon material using waste lithium-ion battery positive electrode materials and using the carbon material for adsorbing hydrogen bromide, characterized in that it comprises the following steps:

[0008] (1) preparing a low eutectic solvent, mixing the low eutectic solvent and the lithium ion battery positive electrode material at a mass ratio of 45 to 55:1 at 110 to 130° C. for 23 to 25 hours to obtain a mixed solution, and then centrifuging to obtain a leachate;

[0009] The mass ratio of the above-mentioned low eutectic solvent to the lithium ion battery positive electrode material is 45 to 55:1, for example, it can be 45:1, 46:1, 47:1, 48:1, 49:1, 50:1, 51:1, 52:1, 53:1, 54:1 or 55:1, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0010] (2) mixing the biomass and the leaching solution in a mass ratio of 1:1 to 1:4, and calcining at 400 to 600° C. for 1.5 to 3 hours to obtain a carbon material;

[0011] The mass ratio of the above biomass to the extract is 1:1 to 1:4, for example, it can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0012] (3) Using carbon materials to adsorb hydrogen bromide gas or hydrogen chloride gas, the adsorption temperature is 25 to 60°C, and the adsorption time is 24 to 72 hours.

[0013] Furthermore, in the step (1), lactic acid and the hydrogen bond acceptor are mixed in a molar ratio of 1:10 to 1:14, and stirred at 60° C. until fully dissolved to prepare a low eutectic solvent;

[0014] Wherein, the hydrogen bond acceptor is valine or leucine.

[0015] The molar ratio of lactic acid to hydrogen bond acceptor is 1:10 to 1:14, for example, 1:10, 1:11, 1:12, 1:13 or 1:14, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0016] Preferably, lactic acid and valine are mixed in a molar ratio of 1:10, and stirred at 60° C. until fully dissolved to prepare a deep eutectic solvent;

[0017] Preferably, lactic acid and valine are mixed in a molar ratio of 1:12, and stirred at 60° C. until fully dissolved to prepare a deep eutectic solvent;

[0018] Preferably, lactic acid and valine are mixed in a molar ratio of 1:14, and stirred at 60° C. until fully dissolved to prepare a deep eutectic solvent;

[0019] Preferably, lactic acid and leucine are mixed in a molar ratio of 1:10 and stirred at 60° C. until fully dissolved to prepare a deep eutectic solvent;

[0020] Preferably, lactic acid and leucine are mixed in a molar ratio of 1:12, and stirred at 60° C. until fully dissolved to prepare a deep eutectic solvent;

[0021] Preferably, lactic acid and leucine are mixed in a molar ratio of 1:14 and stirred at 60° C. until fully dissolved to prepare a low eutectic solvent.

[0022] Furthermore, in the step (1), a low eutectic solvent and a lithium-ion battery positive electrode material in a mass ratio of 50:1 are mixed and stirred at 120° C. for 24 hours to obtain a mixed solution.

[0023] Furthermore, in step (1), the mixed solution is centrifuged at a centrifugal rate of 12,000 revolutions per minute for 20 minutes, and the supernatant after centrifugation is the leachate.

[0024] Furthermore, the positive electrode material of the lithium-ion battery is lithium cobalt oxide or lithium iron phosphate.

[0025] Preferably, a low eutectic solvent having a mass ratio of 50:1 is mixed with a lithium cobalt oxide positive electrode material at 120° C. for 24 hours to obtain a mixed solution, and the mixed solution is centrifuged at a centrifugal rate of 12,000 revolutions per minute for 20 minutes to obtain a leachate;

[0026] Preferably, a low eutectic solvent having a mass ratio of 50:1 is mixed with a lithium iron phosphate positive electrode material at 120° C. for 24 hours to obtain a mixed solution, and the mixed solution is centrifuged at a centrifugal rate of 12,000 revolutions per minute for 20 minutes to obtain a leachate.

[0027] Furthermore, the biomass is straw or reed; in the step (2), the naturally dried reed waste or straw waste is crushed to obtain reed waste powder or straw waste powder for later use.

[0028] Furthermore, in the step (2), the mixed biomass and the leaching solution are calcined at 500° C. for 2 hours to obtain a carbon material.

[0029] Furthermore, in the step (3), a hydrogen bromide aqueous solution having a mass fraction of 40% hydrogen bromide is poured into a vacuum glass desiccator, and then an appropriate amount of carbon material is added, and the mixture is heated to an adsorption temperature of 25 to 60° C., and the carbon material is used to adsorb hydrogen bromide gas for a time of 24 to 72 hours, and the adsorption efficiency is calculated; or,

[0030] Pour a hydrochloric acid aqueous solution with a mass fraction of hydrogen chloride of 37% into a vacuum glass desiccator, then put in a carbon material, heat it to an adsorption temperature of 25 to 60°C, use the carbon material to adsorb hydrogen chloride gas, the adsorption time is 24 to 72 hours, and calculate the adsorption efficiency.

[0031] Furthermore, the adsorption efficiency of the carbon material for hydrogen bromide gas is 20% to 50%, and the adsorption efficiency of the carbon material for hydrogen chloride gas is 20% to 50%.

[0032] Beneficial effects of the present invention:

[0033] The invention provides a method for preparing a carbon material by utilizing waste lithium ion battery positive electrode materials and using the carbon material for adsorbing hydrogen bromide, which is a green resource utilization of waste lithium ion battery positive electrode materials and can realize efficient adsorption of hydrogen bromide.

[0034] The method uses biomass and lithium-ion battery positive electrode material leachate as raw materials, calcines to obtain carbon materials, and uses the prepared carbon materials to adsorb hydrogen bromide gas under mild conditions. It can not only solve the existing resource waste and environmental pollution problems, and has the advantages of being green and environmentally friendly, simple to operate, mild conditions, and low cost, but also has important practical application value for the resource utilization of lithium-ion battery positive electrode material leachate and reed and straw waste. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with the embodiments, and the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] In the following examples, unless otherwise specified, the operating methods used are all conventional operating methods; the materials, reagents, etc. used are all available from commercial channels; and the equipment used are all conventional equipment.

[0037] The biomass used in the following examples is reed waste from Baiyangdian Lake and straw waste from rural areas in the Beijing-Tianjin-Hebei region.

[0038] Example 1

[0039] This embodiment provides a method for preparing a carbon material using a cathode material of a waste lithium-ion battery, the steps are as follows:

[0040] Add valine and lactic acid in a molar ratio of 1:12 into a reagent bottle, stir at 60°C until fully dissolved to synthesize a deep eutectic solvent;

[0041] Add 0.1 g of lithium cobalt oxide positive electrode material and 5 g of low eutectic solvent to a screw bottle, place it in an oil bath, and stir and dissolve it at 120°C for 24 hours. Transfer the mixed solution to a centrifuge tube and centrifuge it at 12,000 rpm for 20 minutes. The supernatant after centrifugation is the leachate. Grind the reed waste into powder, mix the reed powder with the leachate in a mass ratio of 1:2, put it into a crucible and transfer it to a muffle furnace, calcine it at 500°C for 2 hours, and obtain a carbon material after calcination. Grind the carbon material and place it in a reagent bottle for storage.

[0042] This embodiment also provides a method for using the carbon material prepared above to adsorb hydrogen bromide, the steps are as follows:

[0043] Add 110 g of aqueous hydrogen bromide solution (mass fraction of hydrogen bromide is 40%) into the vacuum dryer, place a weighing bottle containing 0.03 g of carbon material on the porcelain plate of the vacuum dryer, evacuate the vacuum dryer, and then place it in a constant temperature oil bath at 60°C for heating, using the carbon material to adsorb hydrogen bromide gas for 24 hours.

[0044] In order to eliminate the systematic error brought by the weighing bottle in this experiment, a blank test was carried out while the experimental conditions remained unchanged. 110 grams of hydrogen bromide aqueous solution (hydrogen bromide mass fraction is 40%) was added to the vacuum dryer, and the weighing bottle without carbon material was placed above the porcelain plate of the vacuum dryer. After the vacuum dryer was evacuated, it was kept at a constant temperature of 60°C in a constant temperature oil bath for 24 hours.

[0045] The adsorption rate was calculated using the change in the total mass of the carbon material before and after adsorption. The adsorption efficiency of the carbon material for hydrogen bromide gas was calculated to be 37.46%.

[0046] Example 2

[0047] The difference between this embodiment and embodiment 1 is that the biomass for synthesizing carbon materials is changed from reed waste to straw waste, while other conditions remain unchanged.

[0048] The adsorption efficiency of the carbon material for hydrogen bromide gas is 45.95%.

[0049] Some parameters of Example 1, Example 2 and Examples 3-17 are shown in Table 1.

[0050] Example 3

[0051] The difference between this embodiment and embodiment 1 is that the type of positive electrode material is changed from lithium cobalt oxide to lithium iron phosphate. Other conditions remain unchanged.

[0052] The adsorption efficiency of the carbon material for hydrogen bromide gas is 41.78%.

[0053] Example 4

[0054] The difference between this embodiment and embodiment 1 is that the adsorption temperature is changed from 60° C. to 25° C. The other conditions remain unchanged.

[0055] The adsorption efficiency of the carbon material for hydrogen bromide gas is 23.84%.

[0056] Example 5

[0057] The difference between this embodiment and embodiment 1 is that the adsorption object of the carbon material is changed from hydrogen bromide aqueous solution (hydrogen bromide mass fraction is 40%) to hydrochloric acid aqueous solution (hydrogen chloride mass fraction is 37%). Other conditions remain unchanged.

[0058] The adsorption efficiency of the carbon material for hydrogen chloride gas is 21.71%.

[0059] Example 6

[0060] The difference between this embodiment and embodiment 1 is that the adsorption time is changed from 24 hours to 48 hours, while other conditions remain unchanged.

[0061] The adsorption efficiency of the carbon material for hydrogen bromide gas is 39.09%.

[0062] Example 7

[0063] The difference between this embodiment and embodiment 1 is that the adsorption time is changed from 24 hours to 72 hours, while other conditions remain unchanged.

[0064] The adsorption efficiency of the carbon material for hydrogen bromide gas is 40.72%.

[0065] Example 8

[0066] The difference between this embodiment and embodiment 2 is that the mass ratio of the biomass of the synthetic carbon material to the leaching solution is changed from 1:2 to 1:4. Other conditions remain unchanged.

[0067] The adsorption efficiency of the carbon material for hydrogen bromide gas is 31.56%.

[0068] Example 9

[0069] The difference between this embodiment and embodiment 2 is that the mass ratio of the biomass of the synthetic carbon material to the leaching solution is changed from 1:2 to 1:1. Other conditions remain unchanged.

[0070] The adsorption efficiency of the carbon material for hydrogen bromide gas is 31.25%.

[0071] Example 10

[0072] The difference between this embodiment and embodiment 2 is that the type of positive electrode material is changed from lithium cobalt oxide to lithium iron phosphate. Other conditions remain unchanged.

[0073] The adsorption efficiency of the carbon material for hydrogen bromide gas is 31.58%.

[0074] Embodiment 11

[0075] The difference between this embodiment and embodiment 2 is that the adsorption temperature is changed from 60° C. to 25° C. The other conditions remain unchanged.

[0076] The adsorption efficiency of the carbon material for hydrogen bromide gas is 33.22%.

[0077] Example 12

[0078] The difference between this embodiment and embodiment 2 is that the adsorption object of the carbon material is changed from hydrogen bromide aqueous solution (hydrogen bromide mass fraction is 40%) to hydrochloric acid aqueous solution (hydrogen chloride mass fraction is 37%). Other conditions remain unchanged.

[0079] The adsorption efficiency of the carbon material for hydrogen chloride gas is 20.00%.

[0080] Embodiment 13

[0081] The difference between this embodiment and embodiment 2 is that the adsorption time is changed from 24 hours to 48 hours. Other conditions remain unchanged.

[0082] The adsorption efficiency of the carbon material for hydrogen bromide gas is 47.57%.

[0083] Embodiment 14

[0084] The difference between this embodiment and embodiment 2 is that the adsorption time is changed from 24 hours to 72 hours, while other conditions remain unchanged.

[0085] The adsorption efficiency of the carbon material for hydrogen bromide gas is 49.19%.

[0086] Embodiment 15

[0087] The difference between this embodiment and embodiment 2 is that the molar ratio of the deep eutectic solvent components is changed from 1:12 to 1:10. Other conditions remain unchanged.

[0088] The adsorption efficiency of the carbon material for hydrogen bromide gas is 20.13%.

[0089] Example 16

[0090] The difference between this embodiment and embodiment 2 is that the molar ratio of the deep eutectic solvent components is changed from 1:12 to 1:14. Other conditions remain unchanged.

[0091] The adsorption efficiency of the carbon material for hydrogen bromide gas is 33.55%.

[0092] Embodiment 17

[0093] The difference between this embodiment and embodiment 2 is that the hydrogen bond acceptor of the deep eutectic solvent is changed from valine to leucine, while other conditions remain unchanged.

[0094] The adsorption efficiency of the carbon material for hydrogen bromide gas is 28.38%.

[0095] Table 1 Adsorption efficiency of carbon materials of Examples 1-17

[0096]

[0097]

[0098] The above description is only a preferred embodiment of the present invention, and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, modification, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing carbon material using waste lithium-ion battery positive electrode material and using it to adsorb hydrogen bromide, characterized in that: The following steps are involved: (1) preparing a low eutectic solvent, mixing the low eutectic solvent and the lithium ion battery positive electrode material at a mass ratio of 45 to 55:1 at 110 to 130° C. for 23 to 25 hours to obtain a mixed solution, and then centrifuging to obtain a leachate; (2) mixing the biomass and the leaching solution in a mass ratio of 1:1 to 1:4, and calcining at 400 to 600° C. for 1.5 to 3 hours to obtain a carbon material; (3) Using carbon materials to adsorb hydrogen bromide gas or hydrogen chloride gas, the adsorption temperature is 25 to 60°C, and the adsorption time is 24 to 72 hours.

2. The method according to claim 1, characterized in that In the step (1), the hydrogen bond acceptor and lactic acid are mixed in a molar ratio of 1:10 to 1:14, and stirred at 60° C. until fully dissolved to prepare a low eutectic solvent; Wherein, the hydrogen bond acceptor is valine or leucine.

3. The method according to claim 1, characterized in that: In the step (1), a low eutectic solvent and a lithium-ion battery positive electrode material in a mass ratio of 50:1 are mixed and stirred at 120° C. for 24 hours to obtain a mixed solution.

4. The method according to claim 1, characterized in that: In the step (1), the mixed solution is centrifuged at a centrifugal rate of 12,000 revolutions per minute for 20 minutes, and the supernatant after centrifugation is the leaching solution.

5. The method according to claim 1, characterized in that The positive electrode material of the lithium-ion battery is lithium cobalt oxide or lithium iron phosphate.

6. The method according to claim 1, characterized in that The biomass is straw or reed; in the step (2), the naturally dried reed waste or straw waste is crushed to obtain reed waste powder or straw waste powder for later use.

7. The method according to claim 1, characterized in that In the step (2), the mixed biomass and the leaching solution are calcined at 500° C. for 2 hours to obtain a carbon material.

8. The method according to claim 1, characterized in that In the step (3), a hydrogen bromide aqueous solution with a hydrogen bromide mass fraction of 40% or a hydrochloric acid aqueous solution with a hydrogen chloride mass fraction of 37% is poured into a vacuum glass desiccator, and then a carbon material is placed in it, and the mixture is heated to an adsorption temperature of 25 to 60° C. The carbon material is used to adsorb hydrogen bromide gas or hydrogen chloride gas for a time of 24 to 72 hours, and the adsorption efficiency is calculated.

9. The method according to claim 8, characterized in that The adsorption efficiency of the carbon material for hydrogen bromide gas is 20% to 50%, and the adsorption efficiency of the carbon material for hydrogen chloride gas is 20% to 50%.